2021
DOI: 10.31258/raje.4.2.105-118
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan limbah sampah sebagai media pembelajaran agama Islam pada anak usia dini di tengah pandemic Covid-19

Abstract: The existence of the co-19 pandemic is the cause of the implementation of large-scale social restrictions (PSBB), which resulted in almost all Indonesian people can only carry out their activities at home. As a result of the high activity being carried out at home, the by-products in the form of garbage also increased a lot. Both organic and inorganic waste, which often cannot be utilized. On the other hand, the educational process that usually occurs in schools now has to move to the house, with the mother ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Utilization of waste building materials into stalls is a breakthrough in realizing sustainable green development, especially being able to encourage and improve business and the people's economy for the better. Confirmed by (Mallapiang et al, 2020;Rohita et al, 2021) revealed that organic or inorganic waste can certainly be utilized, (Fauzi et al, 2020) for community empowerment in processing waste into something of value is the key to the success of the program. However, seeing and realizing that the understanding and ability of the people of Joglo Sub-district to utilize the green fashion concept in creating clothing art designs that are environmentally friendly and of economic value have not met expectations.…”
Section: Hamdan Et Al Names 151mentioning
confidence: 99%
“…Utilization of waste building materials into stalls is a breakthrough in realizing sustainable green development, especially being able to encourage and improve business and the people's economy for the better. Confirmed by (Mallapiang et al, 2020;Rohita et al, 2021) revealed that organic or inorganic waste can certainly be utilized, (Fauzi et al, 2020) for community empowerment in processing waste into something of value is the key to the success of the program. However, seeing and realizing that the understanding and ability of the people of Joglo Sub-district to utilize the green fashion concept in creating clothing art designs that are environmentally friendly and of economic value have not met expectations.…”
Section: Hamdan Et Al Names 151mentioning
confidence: 99%
“…The proposed activity is specifically carried out to provide knowledge about the basic understanding, technology and process of energy storage. The use of local resources can be make positive opinions about the existence of energy storage and biomass supporting the technology (Rohita et al, 2021).…”
Section: Introductionmentioning
confidence: 99%